Testing nonlinear dynamics, long memory and chaotic behaviour with macroeconomic data - Kari Takala; Matti Virén (Bank of Finland, 1995)
This paper contains a set of tests for nonlinearities in economic time series.The tests correspond both to standard diagnostic tests for revealing nonlinearities and some new developments in modelling nonlinearities.The latter test procedures make use of models in chaos theory, so-called long-memory models and some asymmetric adjustment models. Empirical tests are carried out with Finnish monthly data for ten macroeconomic time series covering the period 1920-1994. Test results support unambiguously the notion that there are strong Nonlinearities in the data.The evidence for chaos, however, is weak.Nonlinearities are detected not only in a univariate setting but also in some preliminary investigations dealing with a multivariate case.Certain differences seem to exist between nominal and real variables in nonlinear behaviour.Also in terms of short and long-term behaviour some differences can be detected.
URN:NBN:fi:bof-20140807635
Keywords: 330